2012
DOI: 10.1007/s00280-012-1963-2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic study of omacetaxine mepesuccinate administered subcutaneously to patients with advanced solid and hematologic tumors

Abstract: PurposeOmacetaxine mepesuccinate is a first-in-class cephalotaxine demonstrating clinical activity in chronic myeloid leukemia. A subcutaneous (SC) formulation demonstrated efficacy and safety in phase 1/2 trials in patients previously treated with ≥1 tyrosine kinase inhibitor. This study assessed pharmacokinetics and safety of SC omacetaxine in patients with advanced cancers.MethodsOmacetaxine 1.25 mg/m2 SC was administered BID, days 1–14 every 28 days for 2 cycles, until disease progression or unacceptable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 24 publications
(21 reference statements)
2
29
0
Order By: Relevance
“…The elimination of omacetaxine, 4′-DMHHT, and cephalotaxine in urine was moderately slow, with the majority excreted within 36 h postdose. The excretion data reported here for omacetaxine, 4′-DMHHT, and cephalotaxine within the first 24 h after administration correspond to results reported previously by Nemunaitis et al, who found urinary excretion of omacetaxine, 4′-DMHHT, and cephalotaxine to be 12 to 15 %, 4 to 5 %, and 0.07 %, respectively [17]. The recovery of TRA in 72 h was slightly higher than the sum of the recoveries of omacetaxine and its two metabolites over this same period (35.2 % versus 30.3 %), suggesting that other 14 C-omacetaxine-derived materials may be present.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The elimination of omacetaxine, 4′-DMHHT, and cephalotaxine in urine was moderately slow, with the majority excreted within 36 h postdose. The excretion data reported here for omacetaxine, 4′-DMHHT, and cephalotaxine within the first 24 h after administration correspond to results reported previously by Nemunaitis et al, who found urinary excretion of omacetaxine, 4′-DMHHT, and cephalotaxine to be 12 to 15 %, 4 to 5 %, and 0.07 %, respectively [17]. The recovery of TRA in 72 h was slightly higher than the sum of the recoveries of omacetaxine and its two metabolites over this same period (35.2 % versus 30.3 %), suggesting that other 14 C-omacetaxine-derived materials may be present.…”
Section: Discussionsupporting
confidence: 90%
“…After administration, the observed pharmacokinetic profiles of omacetaxine and 4′-DMHHT were consistent with results from a previous study in patients with cancer [17]. The high apparent volume of distribution suggests that omacetaxine is distributed extensively into the tissues; this is consistent with previous reports in which the drug was administered either as a subcutaneous injection or an intravenous infusion [17, 23].…”
Section: Discussionsupporting
confidence: 90%
“…However, regarding pharmacokinetics only one report is available (18) for the subcutaneous (sc) omacetaxine. Two inactive drug metabolites have been identified, however, for omacetaxine, after sc 1.25 mg/m 2 b.i.d.…”
Section: Pharmacokinetics Of Omacetaxinementioning
confidence: 99%
“…During the treatment of elderly patients with long-term low dose chemotherapy, non-hematological toxicity from HBT has not been found (32,(38)(39)(40)(41). Previous studies have identified cases of grade 4 left bundle branch block during HBT therapy, or grade 2 QT interval prolonged (42), which was not associated with the blood concentration of HBT (43). In the current study, the non-hematological toxicity adverse reactions from HBT treatment were minimal and considered acceptable, and the typical level 3-4 adverse reaction that was detected was hematological toxicity.…”
Section: Discussionmentioning
confidence: 99%